Development of a Training Curriculum to Enhance Research Culture in Learning Management for Primary School Teachers Under Buengkan Primary Educational Service Area Office - ชัยมูล อรรถกร; กำจัดภัย สำราญ; ปราบหงษ์ อุษา (Journal of Educational Review Faculty of Education in MCU, 2019)
The purposes of this research were: ๑) to study the components and indicators of the research culture in the learning management of primary school teachers, ๒) to study the state, expectations and needs of enhancing the research culture in the learning management of primary school teachers, ๓) to develop a training curriculum to enhance the research culture in the learning management of primary school teachers, and ๔) to study the results of experiment in using the developed curriculum. A sample used in the study of state and expectations of the research culture in the learning management was ๓๒๗ primary school teachers under the Office of Bueng Kan Primary Education Service area in academic years ๒๐๑๗, who were selected by multi-stage random sampling and whose size was determined using Krejcie and Morgan Table. The sample used in experiment of using the curriculum was ๑๔ primary school teachers in the Non Sawang Pong Pueai Khaisi School Group under the Office of Bueng Kan Primary Education Service Area in academic year ๒๐๑๗, which were derived from purposive selection on a voluntary basis. The instruments used in the study were a questionnaire of state and expectations of the research culture, a curriculum, a manual for the use of the curriculum, a test of the research culture in the management of learning on research knowledge, an assessment form of beliefs about research, an assessment form of the use of research in learning management, and an assessment form of teachers’ satisfaction with the curriculum. Statistics used in data analysis were percentage, mean, standard deviation, and Wilcoxon signed-ranks test. Findings of the study were as follows: ๑. The research culture in the learning management had ๓ components and ๔๕ indicators. Component ๑ – knowledge about research in the learning management comprising ๑๓ indicators; component ๒ – beliefs about research comprising ๑๘ indicators; component ๓ – use of research in the management of learning regularly comprising ๑๔ indicators. ๒. The results of studying the state, expectations and needs showed that the overall state was at low level (= ๑.๘๑, S.D. = ๐.๑๗), the overall expectation was at the highest level (= ๔.๕๕, S.D. = ๐.๐๙), and the needs of all the components had the values of PNImodified higher than ๐.๓๐. ๓. The developed training curriculum had ๘ components: ๑) background, ๒) principles, ๓) objectives, ๔) research culture components, ๕) content structure, ๖) activities, ๗) media and sources of learning, and ๘) measurement and evaluation. The content structure consisted of ๗ units. Unit ๑ – orientation of ‘how are the teachers who have a culture of research’; unit ๒ – research and management of learning; unit ๓ – how to get started with research in learning management; unit ๔ – how to make research successful; unit ๕ – composing and presenting the success of research in learning management; unit ๖ – putting knowledge into research practice in real situations; unit ๗ – seminar on evaluation and conclusion of training by training at the ๓-day training room (๑๘ hours) and practicing doing research at the school for ๔ weeks. Use training activities as a basis for school-based, reflection and adult learning. ๔. The results of experiment in using the curriculum found the following: ๔.๑ The research culture on teacher knowledge after the training was significantly higher than that before the training at the .๐๕ level. ๔.๒ The research culture on beliefs about teacher research after the training was significantly higher than that before the training at the .๐๕ level. ๔.๓ The research culture on the use of research in the regular learning management of teachers after the training was at the highest level (= ๔.๕๔, S.D. = ๐.๑๘) and higher than the criterion set at ๓.๕๑. ๔.๔ The teachers’ satisfaction with the use of the training curriculum was at the highest level (= ๔.๕๕, S.D. = ๐.๐๘).